IDENTITAS BUDAYA PADA MAHASISWA BATAK TOBA YANG KULIAH DI MEDAN - Nauly, Meutia; Fransisca, Vivi (Konsorsium Psikologi Ilmiah Nusantara (KPIN), 2015)
Abstract — The phenomenon that underlies the condition of Batak students who grew up in the city of Medan, which no longer uses the language batak, even with their own families, and a lack of understanding for the value of the main culture Bataknese, namely Hamoraon, Hagabeon and Hasangapon and understanding Dalihan na tolu as a concept family relationship in the Batak, raised a main concern of this study. This was a non-experimental and comparison study that aimed to find differences of cultural identity, which consists various aspects, including: perception, importance, esteem, maintenance and behavioral expression, on Batak Toba students who enrolled at the University of North Sumatra, in terms of where the subjects were raised. Results of the data analysis showed the existence of significant difference of the cultural identity in student's Batak Toba, who enrolled at the University of North Sumatra, in terms of where the subject was raised – between the ones who were born and raised in Batak Toba and within the city of Medan. The results shows that cultural identity of students who were born and raised in Batak Toba tends to be stronger than the one possessed by students who were born and raised from the city of Medan. It expressed the need to keep transmitting these values to the younger generation, so that these values remain intact. Abstrak — Penelitian ini diawali dengan semakin banyaknya ditemukan mahasiswa Batak yang dibesarkan di Kota Medan, yang tidak lagi menggunakan bahasa Batak, bahkandengan keluarga mereka sendiri,dan kurangnya pemahaman akan nilai budaya utama Orang Batak, yakni Hamoraon, Hagabeon dan Hasangapon serta pemahaman akan Dalihan na Tolu sebagai konsep hubungan kekeluargaan pada orang Batak. Penelitian ini merupakan penelitian komparasi non eksperimental yang bertujuan untuk mengetahui perbedaan identitas budaya yang terdiri dari aspek perception, importance, esteem, maintenance dan behavioral expression pada mahasiswa Batak Toba yang berkuliah di Universitas Sumatera Utara, ditinjau dari tempat subjek dibesarkan. Hasil analisa data menunjukkan adanya perbedaan identitas budaya pada mahasiswa Batak Toba yang berkuliah di Universitas Sumatera Utara, ditinjau dari tempat subjek dibesarkan, dalam hal ini antara yang lahir dan besar di Tanah Batak Toba dan yang lahir dan besar di Kota Medan.Identitas budaya mahasiswa yang lahir dan besar di Tanah Batak Toba lebih kuat dibandingkan yang dimiliki oleh mahasiswa yang lahir dan besar di Kota Medan.Diutarakan adanya kebutuhan untuk tetap mentransmisikan nilai-nilai budaya terhadap generasi muda, agar nilai-nilai ini tetap terjaga.